An An EFL Textbook Evaluation for Grade Ten Used in Takhassus Alquran Vocational School Wonosobo - Abdur Rofik (CLLiENT (Culture, Literature, Linguistics, and English Teaching), 2020)
Textbooks of EFL have an essential role in language learning input for students in classroom activities. Unfortunately, selection and evaluation of EFL textbooks sometimes get a little attention and consideration in language teaching contexts. This study aims to evaluate an EFL selected textbook for grade ten students in Takhassus Alquran Vocational School Wonosobo based on Cunningsworth’s book criteria (1995). The book is Kurikulum 2013 Bahasa Inggris revised edition 2017. This is a qualitative method proposing content analysis. Hence, the results are descriptive qualitative forms. The study uncovers that Bahasa Inggris Kurikulum 2013 textbook fulfills the book criteria proposed by Cunningswoth. Particularly in terms of aims and approaches, design and organization, language contents, topics, methodology, practical consideration. Furthermore, the book needs to be developed in one main aspect, namely skills, particularly listening comprehension. Additionally, the book needs to improved vocabulary materials to faciliate vocational school students’ needs.